Reflexões e (res)significações do currículo de língua inglesa no ensino médio integrado do Instituto Federal de Brasília - Santos, Jane Beatriz Vilarinho dos (2018)
This thesis proposes the problematization of the English language curriculum of the Integrated High School courses of the Federal Institute of Brasília (IFB). Thus, based on the curriculum theories (LOPES; MACEDO, 2010, SILVA, 2014) that guide teaching in this context and oriented by a critical perspective that seeks to problematize "truths", I discuss the English curriculum of this institution. The present studies of Applied Linguistics (PENNYCOOK, 2006; MOITA LOPES, 2006; CALVALCANTI, 2006) emphasize the need and the relevance of problematizing naturalized or hegemonic conceptions, considering that all knowledge is situated and based on power relations. This concern is also present in the area of the curriculum. Moreira and Silva (2009), for instance, stresses that in order to propose new curricular objectives or to transgress current proposals, it is necessary to denaturalize and historicize the curriculum. Being aware of this need, I propose the following thesis: the English Language curriculum of Integrated High-school courses in IFB is guided by a modern conception of knowledge and requires (re)signification. I develop this study based on the principles of qualitative research (DENZIN; LINCOLN, 2013) in order to answer two questions: 1- What are the meanings or curriculum theories that support the English language curriculum of the IFB? 2- What are the possible meanings for the teaching of English in Integrated High-school courses (EMI) of the IFB in the current context? To discuss these ideias, I analyse institutional curricular documents, interviews with teachers and reflective sessions with students and teachers. In the group of participants of this study, there are five English teachers and thirty-one English students. My reflections on the empirical material of this study show that the English curricula of Integrated High school courses of the IFB are guided by hybrid curriculum theories, showing precepts of traditional, critical, and post-critical theories (SILVA, 2014). This hybridity of meanings shows the fluidity of concepts in postmodernity, as well as the complex and controversial nature of educational policies, which are present from their inception to their implementation (MAINARDES, 2006). This nature reminds me of an understanding of the curriculum and the school as spaces of struggles and resistances for the construction of the educational senses, both of which can be constituted as more or less democratic places of production or reproduction of meanings. Therefore, I argue that its problematization is paramount in an educational practice socially committed to local demands and needs. As for the English language teaching and curriculum in the current context of reform, I believe that law 13.415 (BRAZIL, 2017) is a setback in establishing English as the only compulsory foreign language in secondary education, since it restricts and reduces students’ basic education, mainly in public schools. This obligation contributes to differentiate public and private education even more, since the latter will offer other languages in their curricula, because of its financial resources, and thus provide a better education. This normalization, which is strongly criticized by the scholars of Applied Linguistics for disregarding the local demands of students’ education and the multilingualism (SZUNDY ET AL., 2016) that characterizes our country, also contradicts the proposal of curriculum flexibilization, one of the main justifications of this reform. Finally, I argue that the law 13.415 is part of the new modes of governance of the public sector (BALL, 2008), echoing a mercantile view of education and foreign language teaching, and thus becomes an attempt to social, curricular and educational control.